Application of Short-Term Ovulating Synchronization and Fixed-Time Artificial Insemination Protocol to Enhance Pregnancy Rates in Lactating Dairy Cows - Wilasinee Pirokad (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Improving efficiency of synchronization protocols for ovulation and fixed-time artificial insemination (fixed-time AI) is essential to improve female reproductive ability in dairy cattle. Hormonal protocols for synchronization of ovulation and fixed-time AI, with a combination of progesterone (P4), prostaglandin F2α (PGF2α), gonadotropin releasing hormone (GnRH), and estradiol (E2), attempt to induce a new dominant follicle, luteal function, and ovulation at a designated time. Moreover, the low fertility of dairy cows during heat stress, they have been classified as repeat breeding cows that do not become pregnant until the third or remain infertile after numerous inseminations. As result, inadequate P4 concentrations during the luteal phase result in reduction of fertility in dairy cows. The induction of accessory corpus luteum (CL) on ovary by GnRH represents one important method to improve endogenous P4 concentration during the luteal phase. Therefore, the aims of the present thesis were 1) to evaluate the administrations of GnRH at the initiation of the short-term (5 days) ovulating synchronization protocol, at AI, and 5 days after AI on estrous and ovulatory responses, pregnancy rate, and P4 concentration in lactating dairy cows and 2) to improve pregnancy rate and reduce embryonic loss by the short-term (5 days) protocol supplemented with GnRH at 5 days after AI in repeat breeding dairy cows, under field condition with a high THI in the northern Thailand. This thesis included two experiments. Experiment 1 was divided in to two sub-experiments as follows. Experiment 1.1: a total of 43 non-pregnant dairy cows were randomized into 4 groups as follows. The 1G + noE group, cows (n=10) were inserted the controlled internal drug release (CIDR) device, into the vagina, for 5 days. On the day of the CIDR withdrawal (Day 5), ﬁrst PGF2α was injected intramuscularly. Continuously, 24 h after ﬁrst PGF2α injection (Day 6), cows were received second PGF2α. On Day 8, cows were received final GnRH. The 1G + yesE group, cows (n=11) received the short-term protocol similar to the 1G + noE group, except adding of E2 on Day 6. The 2G + noE group, cows (n=10) received the short-term protocol similar to the 1G + noE group, except adding of initial GnRH on Day 0. The 2G + yesE group, cows (n=12) received the short-term protocol similar to the 1G + noE group, except adding of initial GnRH on Day 0 and E2 on Day 6. All cows were inseminated 72 h after CIDR withdrawal. The percentage of dairy cows that ovulated after final GnRH injection (on Day 8) was greater (P < 0.05) in 2G + noE group (100.0%) compared with 2G + yesE and 1G + yesE groups (42.9 and 0.0%) but was not different when compared with 1G + noE group (70.0%). Thus, the short-term (5 days) protocol in 2G + noE group was appropriated for ovulating synchronization and fixed-time AI in lactation dairy cows. Experiment 1.2: 32 cows were synchronized with the effective 5-day P4-based protocol from Experiment 1.1 (2G + noE group). To induce the formation of accessory CL, all cows received GnRH injection at 5 days after the end of the synchronization protocol. Based on evaluation of formed CL on ovary, only cows that appeared CL (n=22) were classified into two groups according to number of CLs on ovaries: 1 CL group (original CL on ovary; n=14) and 2 CLs group (original CL + accessory CL on ovaries; n=8). Cows that presented 2 CLs on ovaries had a greater (P < 0.05) maximum concentration of plasma P4 than cows presenting only 1 CL on ovary (16.04 ± 1.60 vs. 13.85 ± 1.13 ng/ml). Experiment 2: 213 repeat breeding cows that raised under field condition with a greater THI (81.7 to 82.4) in the northern Thailand were synchronized with the effective 5-day P4-based protocol from Experiment 1.1 (2G + noE group). All cows were inseminated at 72 h after CIDR withdrawal (on day 0). At 5 days after fixed-time AI, cows were randomly assigned to two groups according to GnRH treatment: control group (n=100) and treatment group (n=113). GnRH-treated cows had greater pregnancy rates at 30 (P = 0.001) and 60 (P = 0.001) days after fixed-time AI, compared with GnRH-untreated cows (49.6 vs. 26.0% and 48.7 vs. 23.0% for 30 and 60 days, respectively). Furthermore, embryonic loss from 30 to 60 days after fixed-time AI tended (P = 0.07) to reduce in cows that received GnRH treatment than in cows that did not receive GnRH treatment (1.8 vs. 11.5%). Conclusion, the short-term (5 days) P4-PGF2α-GnRH-based protocol was appropriated for ovulating synchronization and fixed-time AI in lactation dairy cows. Moreover, the 5-day protocol supplemented with GnRH at 5 days after AI can improve concentration of P4 after AI in lactation dairy cows. Under the field condition of the northern Thailand with a high THI that induce heat stress, application of the short-term (5 days) ovulating synchronization supplemented with GnRH at 5 days after AI can increase pregnancy rate in repeat breeding dairy cows.